2016
DOI: 10.1107/s1600577516004999
|View full text |Cite
|
Sign up to set email alerts
|

Sapphire hard X-ray Fabry–Perot resonators for synchrotron experiments

Abstract: Hard X-ray Fabry-Perot resonators (FPRs) made from sapphire crystals were constructed and characterized. The FPRs consisted of two crystal plates, part of a monolithic crystal structure of Al2O3, acting as a pair of mirrors, for the backward reflection (0 0 0 30) of hard X-rays at 14.3147 keV. The dimensional accuracy during manufacturing and the defect density in the crystal in relation to the resonance efficiency of sapphire FPRs were analyzed from a theoretical standpoint based on X-ray cavity resonance and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In addition to single crystal polycrystals affecting the uniformity of sapphire, the growth method of the sapphire also affects the uniformity. Tsai et al [23] found that optical-grade sapphire grown by the heat exchange method (HEM) had a much lower dislocation density than sapphire grown by the Kylopoulos method (KYM).…”
Section: Materials Selection Considerationmentioning
confidence: 99%
“…In addition to single crystal polycrystals affecting the uniformity of sapphire, the growth method of the sapphire also affects the uniformity. Tsai et al [23] found that optical-grade sapphire grown by the heat exchange method (HEM) had a much lower dislocation density than sapphire grown by the Kylopoulos method (KYM).…”
Section: Materials Selection Considerationmentioning
confidence: 99%
“…Consider the well-known technique of normal-incidence hard X-ray Bragg reflection [14]- [18] which is utilized in, for example, simple two-crystal plate cavity [19]- [24], as well as in multi-cavity [25] [26] Fabry-Perot (FP) resonators when the magnitude of Bragg angle B θ is close to 90˚. The cavities are separated by the crystal plates with specific thickness ratios and, basically, have a common monolithic crystal base.…”
Section: Introductionmentioning
confidence: 99%